Is it rewarding to become carbon neutral? - Schmits, Bernhard Titus (2022)
The world is on the move towards a carbon-neutral era to reduce the impact of climate change. For companies, it is increasingly relevant to participate in this development. My research therefore examines how the announcement of planned climate neutrality affects companies' share prices in the short term. Using the event study methodology, I study market reactions on 117 corporate climate neutrality announcements by publicly traded U.S. companies between 2020 and March 2022. The analysis shows that the companies' share prices respond significantly positive with a 1.43% cumulative average abnormal return (CAAR) in the five days around the announcement. I have further investigated the stock market reactions by clustering the dataset based on company characteristics. I discover that companies that announce stricter carbon reduction targets have a higher cumulative abnormal return (CAR). In addition, companies that declare their carbon neutrality in association with voluntary membership in the Climate Pledge Initiative experience a higher CAR than the announcement without the membership. Finally, a multivariate regression analysis is used to examine whether agency problems influence the level of market reactions. However, no definitive conclusion can be obtained.